The Relationship between Self-Efficacy and HIV/AIDS Prevention Behavior in Adolescents at SMAN 5 Jambi City - Lusi Oktavia Siahaan; Kamariyah Kamariyah; Riska Amalya Nasution; Rts. Netisa Martawinarti; Lisa Anita Sari (International Journal of Health Engineering and Technology, 2026)
HIV/AIDS remains a global public health problem and has a significant impact on adolescents. During this phase, adolescents are vulnerable to risky behaviors that can increase the chance of HIV/AIDS transmission. One psychosocial factor that plays a crucial role in shaping preventive behavior is self-efficacy, which is an individual's belief in their ability to consistently take preventive measures. Low self-efficacy can hinder adolescents from optimally adopting HIV/AIDS preventive behaviors. Therefore, this study aims to analyze the relationship between self-efficacy and HIV/AIDS preventive behaviors among adolescents at SMAN 5, Jambi City.This study used a correlational design with a cross-sectional approach. A sample of 98 respondents was obtained through total sampling. Data collection was conducted using the Self-Efficacy Assessment in HIV Risk Behavior Prevention (EDP2B-HIV) questionnaire and the Sexual Behavioral Abstinence HIV/AIDS Questionnaire (SBAHAQ). Bivariate data analysis was performed using the Gamma correlation test to determine the relationship between self-efficacy and HIV/AIDS preventive behaviors. Univariate analysis showed that the majority of respondents had moderate levels of self-efficacy (71 respondents (71.4%), and moderate levels of HIV/AIDS prevention behavior (48 respondents (48.0%). Bivariate analysis showed a significant relationship between self-efficacy and HIV/AIDS prevention behavior in adolescents (p-value = 0.003; r = 0.551). This finding indicates that the higher the level of self-efficacy in adolescents, the better the HIV/AIDS prevention behavior they implement.Self-efficacy plays a crucial role in shaping and enhancing HIV/AIDS prevention behavior in adolescents. Adolescents with higher levels of self-efficacy tend to demonstrate better and more consistent prevention behavior.